COMPARISON OF OPISTHORCHIASIS DIAGNOSIS VALUES USING THE Ov ANTIGEN RAPID TEST AND FORMALIN-ETHYL ACETATE CONCENTRATION TECHNIQUE IN ĐĂK GLEI DISTRICT, KON TUM 2025 (Vietnam Journal of Community Medicine, 2026)
Background:Liver fluke infection caused by Opisthorchis viverrini is a parasitic disease closely associated with cholangiocarcinoma. In the Central Highlands of Viet Nam, the disease remains endemic; however, local epidemiological data are still limited. A rapid diagnostic test detecting O. viverrini antigen in urine (OV Antigen RDT) has shown potential for community-based screening.Objectives: (1) To determine the prevalence of O. viverrini infection using the Formalin–Ether Concentration Technique (FECT) in Dak Glei district (Kon Tum province) in 2025; (2) To preliminarily compare selected diagnostic performance indicators of the OV Antigen rapid test with FECT.Methods: A cross-sectional descriptive study combined with a diagnostic comparison study was conducted. A total of 403 individuals aged ≥5 years provided stool samples for FECT examination. For the diagnostic comparison, 49 FECT-positive cases and 40 FECT-negative samples were randomly selected for OV Antigen testing using urine specimens. FECT was used as the reference standard.Results: The prevalence of O. viverrini infection by FECT was 12.2% (49/403), with all infections classified as light (
Keywords: Opisthorchis viverrini, Formalin-Ether concentration technique, Ov Antigen rapid test